Identification of Ginger Commodity Potential Areas in Sumatera Utara Province - Francisca Wenny Astriani Widya Sari (Jurnal Agriuma, 2020)
Ginger is a type of multifunctional biopharmaca plant that is in addition to being a spice ingredient in food cooking, it can also be used as a raw material for medicine. Especially in the co-19 pandemic that attack Indonesia today, ginger became the most popular medicinal herbs Â to increase body endurance. This study aims to identify the area of production base of ginger commodity, its distribution characteristics and the role of ginger in supporting regional development in North Sumatra Province. The data used in this study are secondary data from 2017 to 2019. The analysis method used are location quotient analysis, localization and specialization analysis, basic service ratio analysis and regional multiplier analysis. The results showed that the ginger base commodity based on production indicators in North Sumatra Province included South Tapanuli District, Toba Samosir District, Karo District, Pakpak Bharat District and Samosir District. Ginger commodity farming in North Sumatra Province is not concentrated in one region, but spread in several districts / cities in North Sumatra Province. Ginger commodity farming in the base regency of North Sumatra Province does not specialize in ginger commodity farming and can participate in supporting biopharmaca agricultural activities in North Sumatra Province.